Empirical Feasibility of an Acoustic Cabin for Reduction the Workers’ Exposure to High Frequency Noise in Typical Metal Industry - ROSTAM GOLMOHAMMADI; MOHSEN ALIABADI (International Journal of Occupational Hygiene, 2016)
Introduction: A practical solution which is sometimes efficient for noise control in the receiver locations is to enclose workers in an acoustic cabin. Accordingly, prediction of the noise insulation performance is regarded as an important aspect of the design a personnel cabin. This study empirically aims to design an acoustic cabin using sandwich panels in a typical metal industry and analyze its effectiveness for reduction the operators’ exposure to high frequency noise. Method: Sheet metal was used as main element of the personnel cabin, and it was coupled with damping materials to achieve efficient noise insulation. The simplified prediction equations were used for prediction of noise transmission loss of the main elements (steel sheet). For design of the cabin sandwich wall, based on the primary prediction results, selection of the other materials and their thickness was performed empirically. Determination of the noise reduction performance of the designed cabin was performed based on in situ measurements. Discussion: The results indicated that all workers were continuously exposed to high noise levels before intervention. However, inside the designed cabin, the exposure levels actually reduced to of 66.6 dB (A) which was much lower than the national exposure limit. The designed cabin showed an overall noise reduction of 20.5 dB (L). Result: The results empirically confirmed where high insulation performance is required; sandwich panels which have adequate mass, low stiffness and high damping can be usually preferred.